Incidence of mushroons in post harvest of banana (Musa spp.) ‘prata ana’ (aab) - Da Silva Moraes, Wilson; Zambolim, Laercio; Lima, Juliana D. [UNESP] (My University, 2006)
The objetive of this work were to determine the occurrence and frequency of fungus in ‘Prata ana’ banana and to elucidate the causal agent of post harvest rots on fruits from Jaiba, Minas Gerais, Brazil. Two isolation methods were used: Diluition in placs from whashed green fruits and direct of mature fruits. The fungus Colletotrichum musae, Trichoderma harzianum, Fusarium equisetii, Penicillium sp., Aspergillus parasiticus, Trichothecium roseum, Colletotrichum acutatum, Alternaria sp., Cladosporium musae and Curvularia lunata were the more frequentilly associated to fruits. The fungus pathogenicity were tested by substituition of green fruits pell discs for micellium discs. Colletotrichum musae showed lesioned average area arround of inoculation point equal to 5,8 cm2, while in the remaining of fungus tested the lesioned average area were smaller than 1,50 cm2. This results showed that C. musae is the primary agent of examined fruits rotteness, with 100% of incidence while the remaining of fungus were limited to attach the injury arround of inoculation point. The latent infection mode caused by C. musae favour firsty the tissue external colonization and after the opportunists fungus accelerate the fruits and crown rotteness.
Incidencia de fungos em pós-colheita de banana ‘prata ana’(Musa aab)
Keywords: Antracnose; Colletotrichum; Disease; Quiescent infection